Description of the female and new records of Triatoma baratai Carcavallo & Jurberg, 2000 (Hemiptera: Heteroptera: Reduviidae: Triatominae) from Mato Grosso do Sul, Brazil, with a key to the species of the Triatoma matogrossensis subcomplex - Obara, Marcos Takashi; Soares Barata, Jose Maria; Da Rosa, Joao Aristeu [UNESP]; Ceretti Junior, Walter; De Almeida, Paulo Silva; Goncalves, Guilmara do Amaral; Dale, Carolina; Gurgel-Goncalves, Rodrigo (Magnolia Press, 2012)
Triatoma baratai Carcavallo & Jurberg, 2000, a species similar to Triatoma williami Galvao, Souza & Lima, 1967 and belonging to the T. matogrossensis subcomplex, was described based on a male specimen collected in a sylvatic environment, near a cave, in Bonito county, Bodoquena mountain range, state of Mato Grosso do Sul, Brazil. In the present work we describe the female of T. baratai, captured in a chicken house, in Nioaque county, state of Mato Grosso do Sul, Brazil. Furthermore, we recorded the occurrence of T. baratai in domiciles and peridomestic environment in another four municipalities (Bodoquena, Bela Vista, Corumba, and Miranda), extending its geographical distribution. Finally, we present a key to the species of the Triatoma matogrossensis subcomplex.
Keywords: Geographical distribution; T. matogrossensis subcomplex; Triatominae